C-Reactive Protein and Matrix Metalloproteinase-7 in Preterm Premature Rupture of Membranes (PPROM) and Premature Rupture of Membranes (PROM): C-Reactive Protein dan Matrix Metalloproteinase-7 pada Ketuban Pecah Dini Kehamilan Preterm dan Aterm - Rajuddin, Rajuddin; Putri, Tgk Chairannisa; Munawar (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective: To determine the difference in qualitative serum CRP and MMP-7 levels between PROM and PPROM Methods: Research with a case-control design with premature rupture of membranes in term pregnancy as a control group and preterm pregnancy as a case group conducted in the delivery room of the Regional General Hospital dr. Zainoel Abidin Banda Aceh starting from January 2020. Total number of each group as many as 30 samples that met the inclusion and exclusion criteria by taking venous blood samples to check the levels of qualitative CRP serum and levels of the Metalloproteinase-7 Matrix (MMP-7). Statistical tests for categorical - numerical data groups were tested using independent sample t-test and categorical - categorical data groups were tested using Chi-Square test. Results: A total of 60 samples with 30 PPROM and 30 PROM mothers. There was no statistically significant difference in the qualitative CRP serum result in PROM patients with term and preterm pregnancies. On MMP-7 examination, the mean MMP-7 level of preterm PROM mothers was higher than at term PROM, which was 5.28 mg / L and there was a significant relationship between MMP-7 and qualitative CRP in PROM patients with term pregnancy (p <0.05). Conclusion: There is no significant difference in the value of qualitative CRP and MMP-7 between PPROM and PROM. However, there was a significant association between qualitative serum CRP and plasma MMP-7 in PROM. Keywords: c-reactive protein, matrix metalloproteinase-7,rupture of membranes. Abstrak Tujuan: Untuk mengetahui perbedaan gambaran serum CRP kualitatif dan kadar MMP-7 antara kehamilan preterm dan aterm dengan ketuban pecah dini di RSUD Dr. Zainoel Abidin Banda Aceh. Metode: Penelitian dengan desain kasus kontrol dengan ketuban pecah dini kehamilan aterm sebagai kelompok kontrol dan kehamilan preterm sebagai kelompok kasus. yang dilakukan di Kamar Bersalin Rumah Sakit Umum Daerah dr. Zainoel Abidin Banda Aceh pada Januari 2020. Dengan jumlah masing-masing kelompok sebanyak 30 sampel yang memenuhi kriteria inklusi dan eklusi dengan pengambilan sampel darah vena untuk dilakukan pemeriksaan kadar serum CRP kualitatif dan kadar Matrix Metalloproteinase-7 (MMP-7). Uji statistik untuk kelompok data yang bersifat kategorik - numerik diuji menggunakan uji T tidak berpasangan dan pasangan kelompok data yang bersifat kategorik - katergorik akan diuji menggunakan uji Chi-Square. Hasil: Sebanyak 60 penderita KPD dengan 30 Ibu KPD Preterm dan 30 KPD aterm. Tidak dijumpai perbedaan yang bermakna secara statistik gambaran serum CRP kualitatif pada penderita KPD dengan kehamilan aterm dan preterm. Pada pemeriksaan MMP-7 rerata kadar MMP-7 ibu KPD preterm lebih tinggi dibandingkan KPD aterm yakni senilai 5,28 mg/L dan terdapat hubungan bermakna antara MMP-7 dan CRP kualitatif pada penderita KPD dengan kehamilan aterm (p < 0,05). Kesimpulan: Tidak terdapat perbedaan gambaran signifikan nilai CRP kualitatif dan MMP-7 antara KPD preterm dan aterm. Namun, terdapat hubungan yang signifikan antara serum CRP kualitatif dan MMP-7 plasma pada penderita ketuban pecah dini dengan kehamilan aterm. Kata kunci: c-reactive protein, matrix metalloproteinase-7, ketuban pecah dini.